2017
DOI: 10.1007/s00125-017-4351-y
|View full text |Cite
|
Sign up to set email alerts
|

Metformin use in pregnancy: promises and uncertainties

Abstract: Metformin has been prescribed in pregnancy for over 40 years; for much of this time, use has been limited both in numbers and geographically, and the evidence base has been confined to observational studies. In early years, perceived safety concerns and lack of availability of the drug in many countries acted as a barrier to use. More recently, RCTs have begun to examine the role of metformin in pregnancy in much-needed detail. However, this evidence base has been interpreted differently in different countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
97
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 51 publications
1
97
0
9
Order By: Relevance
“…However, studies in PCOS suggested that metformin does not increase congenital malformations or miscarriage. In their review, Lindsay and Loeken [28] discuss the use of metformin in gestational diabetes, presenting evidence that metformin has a good safety profile and is effective at reducing rates of severe hypoglycaemia and weight gain in pregnant women. In contrast, however, in pregestational type 2 diabetes the evidence base for metformin use is not strong, but observational evidence suggests increased risk of preeclampsia and perinatal mortality.…”
mentioning
confidence: 99%
“…However, studies in PCOS suggested that metformin does not increase congenital malformations or miscarriage. In their review, Lindsay and Loeken [28] discuss the use of metformin in gestational diabetes, presenting evidence that metformin has a good safety profile and is effective at reducing rates of severe hypoglycaemia and weight gain in pregnant women. In contrast, however, in pregestational type 2 diabetes the evidence base for metformin use is not strong, but observational evidence suggests increased risk of preeclampsia and perinatal mortality.…”
mentioning
confidence: 99%
“…The main mechanism of action is reduction of hepatic glucose production, however several other antidiabetic effects may contribute, including modulation of appetite, modulation of steroidogenesis and AMP kinase activation and effects on the gut microbiota as reviewed in 17,18,20 . Also, metformin influences vitamin B12 absorption 21 , resulting in a 10-30 % reduction of cyanocobalamine levels in general diabetic therapy.…”
Section: Metformin Effects In Generalmentioning
confidence: 99%
“…The compound does cross the placenta, and has been measured in cord blood at a concentration range similar to that in maternal blood 23 . There has also been some concern that a reduction of placental insulin resistance during metformin treatment could influence nutrient transport to the fetus negatively during maternal fast, and result in deficient fetal growth 18 .…”
Section: Metformin Effects In Generalmentioning
confidence: 99%
See 2 more Smart Citations